User Acceptance of Interactive Student Activities Management System: A Proposed Theoretical Model - et. al., Khyrina Airin Fariza Abu SAMAH, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Interactive Student Activities Management System (iSAMS) is a web-based system in Universiti Teknologi MARA Cawangan Melaka that provides information on student bodies and activities. iSAMS developed to react as an integrated management platform during the COVID-19 outbreak since student activities are essential and need to carry out. This research's main objective was to investigate how the iSAMS interface and functions affect users' intentions and attitudes when using the system. Thus, we explored the key predictors of user acceptance of iSAMS and proposed the theoretical model for user acceptance. A conceptual structural model was developed by integrating heuristic evaluation (HE) and technology acceptance model (TAM) to identify which key predictors influence the user acceptance of iSAMS. We adopted HE and TAM in developing the model, and as the outcome, we categorized HE into three categories: system support, user interface design, and navigation. Then, we identified three of TAM’s predictors, which are perceived usefulness, perceived ease of use, and behavioural intention to use. The hypothesis supported each of the predictors as the measurement since we required improvements for the iSAMS usability. The proposed research framework is simple to implement and can be adapted for other developed systems since it is essential in determining the system's usability and user acceptance.